Serum Magnesium in Acute Myocardial Infarction: Observation from Bangladeshi Patients (Faridpur Medical College Journal, 2020)
Dyslipidemia is an established risk factor of acute myocardial infarction (AMI), but measurement of macro metals like magnesium can be helpful in the prevention and better management of AMI. The aim of this study was to estimate serum magnesium in AMI. This is a case control type of study carried out in the Department of Biochemistry, Dhaka Medical College, Dhaka during the period of January 2015 to December 2015 with a total number of 100 study subjects. Acute myocardial infarction patients were selected as case (50) from coronary care unit (CCU), Department of Cardiology, Dhaka Medical College Hospital. Normal healthy individuals were selected as control (50) from the attendants of patients, relatives and doctors. Serum level of magnesium were assessed for both case and control groups. The mean values of the variable were compared between them by statistical analysis using SPSS version 16. For all the statistical analysis P